Is catchment geodiversity a useful surrogate of aquatic plant species richness?. (2nd July 2019) - Toivanen, Maija; Hjort, Jan; Heino, Jani; Tukiainen, Helena; Aroviita, Jukka; Alahuhta, Janne
Abstract: Aim: Conserving freshwater biodiversity in a rapidly changing world requires updated planning schemes and research efforts. Geodiversity – the diversity of Earth surface forms, materials and processes – and biodiversity are interlinked at a fundamental level. This relationship is being considered in a growing number of studies, yet research from freshwater environments is scarce. We used geodiversity (rock‐type, soil‐type and geomorphological richness), local and climatic variables to explore whether geodiversity can be used as a surrogate for aquatic plant species richness in lakes and rivers. Location: Finland. Taxon: Aquatic plants. Methods: We compared geodiversity variables (measured within 1‐km 2 grid cells) to well‐studied local (e.g. area, alkalinity) and climate (e.g. growing degree‐days) variables, and examined the patterns between habitat types (lakes and rivers) and among all taxa and major functional groups (helophytes and hydrophytes). We modelled lake ( n = 145) and river ( n = 146) plant species richness with generalized linear models, and further partitioned variation to measure the independent and shared contributions of the geodiversity, climate and local environmental variable groups. As a complementary analysis, and to identify single important variables explaining variation in aquatic plant species richness, we utilized boosted regression trees. Results: We found a positive relationship between aquatic plant species richness and catchment geodiversity variation with recurring patterns across two different freshwater habitat types and two aquatic plant functional groups. Higher variation in geodiversity (measured at landscape scale) supported higher freshwater biodiversity (measured at the local scale) of lakes and rivers. Main conclusions: Geodiversity can be a useful addition to biodiversity modelling, and it should be considered in conservation schemes and monitoring efforts, further supporting the principle of conserving nature's stage. Yet, differences between habitats and functional groups suggest that more habitat‐specific approaches and multiple biodiversity measures should be considered. Our study is an important signpost guiding further studies on the biodiversity–geodiversity relationship in freshwater ecosystems.